Bridging the gap: The role of assistive technologies in enhancing translation accessibility for visually impaired learners in Moroccan higher educational institutions - Ed-dali, Rachid (Journal of Interdisciplinary Studies in Education, 2025)
This study explores the impact of assistive technologies on academic accessibility for visually impaired students in Moroccan higher education, focusing on translation studies. Using a mixed-methods approach, the research finds that technologies like screen readers are crucial, with 85% of participants using them daily. A strong positive correlation (r = 0.78) is observed between technology use, academic satisfaction, improved task efficiency, and mental health. However, issues with Optical Character Recognition (OCR) software and accessibility barriers persist. The study highlights the need for improved assistive technologies and better-designed educational materials, suggesting further research on their long-term academic and professional impacts.